Top ten caring needs of emergency department patients in Banyumas, Central Java province, Indonesia: patient’s needs and cultural approach - Suroso, Jebul; Soenarto, Yati; Prabandari, Yayi Suryo; Haryanti, Fitri (International Journal of Research in Medical Sciences, 2017)
Background: Nursing care based on characteristic and concept of caring will give positive impact to quality of care. Application of caring in nursing must correspond to local cultural value and patient’s needs. Objective this research explored the caring needs for patients in emergency unit of three district general hospitals (Rumah Sakit Umum Daerah/RSUD) in Banyumas area, Central Java Province, Indonesia. Methods: This need assessment research involved 50 emergency unit patients from three hospitals in Banyumas. Data was collected through interview to complete the list of patient’s caring needs in emergency department. Data were analysed through content analysis, validated by five emergency nursing experts and practitioners. Results: The ten most common caring needs of patients in emergency department included: prompt and responsive care; clear information delivery; friendliness, politeness and fairness; clarity and simplicity of administration; clean and comfortable room; short waiting time for care and admission to ward; competent in procedures; providing care, pray and motivation to patients; complete facility and devices; and room safety. Conclusions: Caring needs of emergency patients in Banyumas area district general hospitals encompass administration, behavioural and enviromental aspects. This result can be considered by hospitals to improve the quality of care in emergency department. Future researches shall be done to acquire more comprehensive measurement tool of caring, involving administration, behavioural and enviromental aspects in emergency department.